A study on the corrosion index of Tap Water(TW) and Reclaimed Water(RW) using KWI(Korea Water Index) and KRWI(Korea Reclaimed Index Water) method - Rasheed, Usman; Lee, Hyundong; Kong, Myeongsik; Kwak, Pilljae (International Journal of Engineering and Technology, 2018)
This study aim to find the corrosion index of Tap water and Reclaimed water using KWI (Korea Water Index) and KRWI (Korea Reclaimed Water Index) method. The impact of corrosion inhibiting factors (pH ,hardness, alkalinity) and corrosion accelerating facor (TDS, chlorine ion, sulphate ion) has studied. The corrosion assessment method based on the corrosion index is used in predicting corrosion and offering information on the control of corrosive water quality.Â Â Â